SAL - Salvatore Scarpitta - Sansone, Luigi 1951-; Miller, Peter Benson (Allemandi, 2024)
SAL, curated by Luigi Sansone, is the catalog of the first retrospective in Rome dedicated to the multiform and pioneering work of Salvatore Scarpitta that traces the creative path of the Italian-American artist, one of the most innovative protagonists of the artistic language of the second half of the 20th century, through some of his most significant works. The double focus of the exhibition is on the Italian period and on the American one: the first takes place in Rome and includes the production of the Expressionist beginnings, the abstract-figurative phase that leads to the Informal of the material paintings, the realization of the extroflexed canvases and - finally - the works with the bands, exhibited at Plinio De Martiis' Galleria La Tartaruga in the historic exhibition held in April 1958. The American period began with an exhibition at Leo Castelli's in New York in January 1959 and ended in 2007, the year of the artist's death. Scarpitta's American phase, which is rich in creative ideas, further develops the theme of the bands and is also oriented in four main directions: the geometric realization of works with the significant ‘St. Andrew's cross’ structure; the vital grafting of materials from the world of car racing into the works with the bands; the construction of racing cars; and the realization of sledges and towing structures inspired by the Native American world
Impressum: Questo catalogo è stato pubblicato in occasione della mostra "SAL", organizzata da Mattia de Luca. - La mostra è stata presentata da Galleria Mattia de Luca, Rome, dal 6 aprile al 21 giugno 2024
Keywords: Scarpitta, Salvatore -- 1919-2007; Ausstellungskatalog -- Mattia de Luca -- 06.04.2024-21.06.2024 -- Rom